Um processo automatizado para tratamento de dados e conceitualização de ontologias com apoio de visualização - Hernandes, Elis Cristina Montoro (2009)
Context: Aiming at collecting data that represent the educational reality of Brasil, from eighteen years the INEP applies census and evaluations on educational institutions. However, this large amount of data is non uniform and distributed among different databases, making difficult more significant analysis. Aiming to solve or minimize these problems, the INEP and Capes are supporting research projects, such as Web-PIDE project, in which this research was carried out. The objective of this project is to create a platform for sharing and integrating these data, which can be used by all the community. Aim: This work had two objectives. The first one was to create a Language for Integration of Educational Data, named LIDE that will support the Web-PIDE platform implementation. The second one was to define a process to support the ontology conceptualization phase, since an ontology can be useful for the INEP evaluation domain. Methodology: Based on visualization it was developed a tool and a process for each objective the SEV-Tool and P-LIDE (Process to definition the Language for Integration Educational Data); and the ONTOP-Tool and ONTOP (ONTOlogy Process). Results: It was created the LIDE|SAEB that will be used in the platform Web-PIDE and it was generated a list of terms that composes a glossary that will support the creation of an ontology for INEP evaluations. Conclusion: The PLIDE process and the SEV-Tool compose a support for the treatment of the INEP evaluation data. The ONTOP process and ONTO-Tool compose a support for ontology conceptualization, in spite of the domain. The use of visualization as the resource for the treatment of these data made easier the execution of the tasks proposed by both processes.